Synthesis of Robust Precursors for the Controlled Fabrication of (6,6), (8,8), (10,10), and (12,12) Armchair Single-Walled Carbon Nanotubes - Mueller, Andreas; Amsharov, Konstantin (European Journal of Organic Chemistry, 2015)
We report an effective strategy for preparing robust precursors for the rational synthesis of helicity-pure single-walled carbon nanotubes (SWCNTs) by a surface-assisted strategy. The approach presented allows simple access to large-diameter SWCNT precursors. The efficiency of the strategy is demonstrated by the synthesis of four robust precursors for the preparation of (6,6), (8,8), (10,10), and (12,12) armchair SWCNTs. The molecules exhibit a rigid and fully fused structure, which is expected to be important for a highly efficient conversion to CNT seeds and a high yield of the respective helicity-pure SWCNTs. The presented synthetic approach provides simple access to robust SWCNT precursors that can be “programmed” for virtually any helicity.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Helicity; Nanotubes; Precursor synthesis; Surface chemistry; Synthesis design